Computational Modeling of Cell Behavior Driven by Growth Factor Release from Biodegradable Microcapsules - Poursaberi, Mahdi; Mousavi, S. Jamaleddin; Doweidar, Mohamed H. (Jornada de Jóvenes Investigadores del I3A, 2025)
Among other stimuli, cell behavior is also regulated by biochemical signals such as growth factors, pharmaceutical agents. Unlike previous models assuming steady gradients, we model the time-dependent release and diffusion of growth factors from degradable microcapsules. Drug diffusion is modeled using Fick’s law with spatially varying diffusivity. The model is validated against previous experimental studies and offers a realistic framework to study localized, controlled drug release and its effect on cell movement.